Propuesta de un modelo didáctico "PSICOMOTRICIDAD" para estimular las áreas de desarrollo de los niños y niñas de tres años de la Institución Educativa del Nivel Inicial "Virgen de la Medalla Milagrosa” del Distrito de Nueva Cajamarca 2011 - Saavedra Córdova, Pamela (2011)
This research called Didactic Proposal for a Model "psychomotor" to stimulate the areas of development of children aged three years from the entry level educational institution "Our Lady of Miraculous Medal" Nueva Cajamarca District 2011. From the perspective of understanding the stimulation exerted by the proposal of a didactic model "psychomotor" in the area of development of children from three years of School of Basic Level "Our Lady of Miraculous Medal" Nueva Cajamarca District 2011 in an educational and pedagogical approach that has as one of its priorities to help develop the teaching-learning process and local levels. Therefore, from the local, from the present research is that the question of which part was raised as follows: To what extent the proposed lnstructional Model "psychomotor" stimulate the areas of child development and girls from three years of School of Basic Level "Our Lady of Miraculous Medal" Nueva Cajamarca District 2011? In this research raises the following problem: This research proposal of a didactic model "psychomotor" to stimulate the areas of development in girls and girls from 3 years of School of Basic Level "Our Lady of the Miraculous Medal." Arises due to the lack of initiative of teachers in the teaching process to encourage their children three years the areas of development in the Personal Social which will al low the child through movement to promote learning. The aim is to better understand the problem and come to serious conclusions by the present research proposal of a didactic model "psychomotor" to stimulate the areas of development in girls and girls from 3 years of School of Basic Level "Our Lady of the Miraculous Medal "by pursuing design and elaborate a proposal of a didactic model" psychomotor "to stimulate the areas of development of children aged three years from the entry level educational institution" Our Lady of Miraculous Medal " in the district of Nueva Cajamarca 2011 . lf hypothesis which is made a proposal of a didactic model "psychomotor" then stimulate the areas of development of children aged three years from the entry level educational institution "Our Lady of Miraculous Medal" Nueva Cajamarca district in 2011 .